IMPLEMENTATION OF CRM SYSTEM IN IMPROVING SERVICE QUALITY AT ZAHRA MART TANJUNGBALAI STORE - Zuhairoh Zuhairoh; Yessica Siagian; Sahren Sahren (Jurnal Teknik Informatika (Jutif), 2022)
Zahra Mart Tanjungbalai is a business that sells various kinds of products ranging from cosmetic products, basic necessities and other goods located on Jl. M. Abbas, No B Lk. VII Ex. Sirantau district. Datuk Bandar Tanjungbalai City. The problem that occurs at Zahra Mart is that it has not implemented a website-based online sales system in marketing its products, and information about the products being sold is still limited, only people around the location know the existence of Zahra Mart Tanjungbalai. Therefore, the application of a CRM system is used to improve service quality at the Zahra Mart Tanjungbalai store which can help buyers find information about the products being sold and make it easier for buyers to place orders without having to come directly to Zahra Mart Tanjungbalai. In this study using qualitative methods that can help researchers to obtain solutions to all problems. The results of this study can help Zahra Mart in marketing their products and expanding sales of the products they market because of the features of rating, promo, discount, cashback, media chat, and service quality assessment (questionnaire). agree with the application of CRM at the Zahra Mart Tanjungbalai store. From the graph, it can be seen that the survey results strongly agree 55.89%, agree 23.72%, disagree 14.12%, strongly disagree 9.42%.